Jet Travel and Desert - Sean Clancy (Etikk i Praksis: Nordic Journal of Applied Ethics)
Jet aircraft produce large quantities of greenhouse gases when in operation, so one way for an agent to reduce her individual greenhouse gas emissions is by reducing the extent to which she flies. Some groups have encouraged agents to give up on flying for life by committing to a “travel pledge”. I argue here that, for many agents, it is morally impermissible to commit to a lifelong travel pledge, because in doing so, they would prevent themselves from receiving what they deserve. Most agents who commit to such a pledge exercise a great deal of virtue, and therefore deserve to have their lives go better, while also making a significant sacrifice, thus ensuring that their lives go worse. Because a single person’s travel pledge cannot make a significant difference to the progress of climate change, the morally desirable effects of such a pledge are outweighed by the morally undesirable effects on desert.